La puissance n'est pas tout ! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
La motorisation dans les cultures tropicales Coédition CTA/CIRAD/Coopération française 1998, 351 pages ISBN 2-87614-322-4, n° CTA 896, 20 unités de crédit